Combinatorial enzyme therapy: A promising neoteric approach for bacterial biofilm disruption. (June 2023) - Upadhyay, Aditya; Pal, Dharm; Kumar, Awanish
Abstract: A closed bacterial loop structure known as the biofilm is affixed to biotic and abiotic surfaces. It provides the survival capacity to the bacterial community in adverse conditions. The bacterial community creates resistance against antibiotics due to biofilm. Thus, biofilm is a major issue to control the infection. Though some conventional and contemporary approaches are available to treat biofilm, however, the available therapies do not give satisfactory results. Hence a novel approach is urgently required to disrupt the mature biofilm. In this direction, combinatorial enzyme therapy could be an efficient solution as compared to other available approaches because of the enzymatic action. Combination processes enhance the enzymatic capacity to disrupt the bacterial biofilm effectively and some studies reported its good biofilm-disrupting potential. The combinatorial enzymatic approach seems promising to disrupt biofilm significantly and could also combat the condition of multi-drug resistance (MDR) effectively. The review discusses the potential and future perspective of various combinatorial enzyme therapies against bacterial biofilm that is effective as compared to the available approach. The article summarized the various effective enzymatic combinations used to disrupt the bacterial biofilm. Thus, combinatorial enzyme therapy could be used as an effective bioweapon to control the biofilm and control infection at the chronic stage. Graphical Abstract: ga1 Highlights: Bacterial biofilm is a global health issue and no potential approach is available to prevent it. Combinatorial enzyme therapy is very close to controlling the bacterial biofilm effectively. It is due to its enhanced enzyme capacity when it is presented in a combination form. The article describes various combinatorial enzymes as a biofilm-disrupting agent. New enzyme combinations could work as a potential key to controlling the bacterial biofilm.